2016
DOI: 10.1186/s12284-016-0108-3
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the oomycete Pythium arrhenomanes and the rice root-knot nematode Meloidogyne graminicola in aerobic Asian rice varieties

Abstract: Background: Aerobic rice fields are frequently infested by pathogenic oomycetes (Pythium spp.) and the rice rootknot nematode Meloidogyne graminicola. Here, the interaction between Pythium arrhenomanes and Meloidogyne graminicola was studied in rice roots of two aerobic rice varieties. In different experimental set-ups and infection regimes, plant growth, rice yield, Pythium colonization, as well as establishment, development and reproduction of M. graminicola were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…These data demonstrate that the JA pathway is induced upon P. arrhenomanes infection in rice roots as part of a plant defense response and lead to the hypothesis that JA induction would be the causal mechanism behind the antagonistic interaction with M. graminicola , reported in Verbeek et al (2016).…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…These data demonstrate that the JA pathway is induced upon P. arrhenomanes infection in rice roots as part of a plant defense response and lead to the hypothesis that JA induction would be the causal mechanism behind the antagonistic interaction with M. graminicola , reported in Verbeek et al (2016).…”
Section: Resultsmentioning
confidence: 67%
“…Previously, we have reported that prior infection by the oomycete P. arrhenomanes consistently reduces the penetration rate and development of the root-knot nematode M. graminicola in rice roots, even under different infection and plant growth conditions (Verbeek et al, 2016). To elucidate a potential mechanism behind this antagonism, we decided to investigate the levels of a set of plant hormones, namely JA, SA, IAA—an important AUX—and ABA, upon single and double inoculations, using root samples taken at two time points (11 and 13 days post germination, dpg) during the greenhouse experiment described in detail in Verbeek et al (2016). Results, shown in Figure 1 , revealed JA levels in the roots are significantly reduced at 3 days post single nematode inoculation (11 dpg) compared to the un-inoculated control ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations